2019
DOI: 10.1021/acs.jpcc.9b04270
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Thermoelastic Anisotropy of the Phenyl Pyrimidine Liquid Crystal

Abstract: Controlling thermoelastic anisotropy of liquid crystals (LCs) is important for achieving reliable structural stability and efficient heat dissipation, especially for high-performance LC devices. A solid understanding of the thermoelastic anisotropy and its relation with the LC molecular structure is, however, still missing. Here, we studied the direction-dependent mechanical and thermal properties of 5- n -octyl-2-(4- n -octyloxy-phenyl)-pyrimidine (PYP8O8) in a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 33 publications
2
17
2
Order By: Relevance
“…Generally, in soft matter, the phonon mean free path is usually lower than a few nanometers; this suggests that the phonon mean free path was not underestimated in our simulations. On the other hand, a recent experimental study of a liquid-crystalline molecule revealed low-frequency phonons to have a long mean free path: in the micrometer range, which may be correlated with the finite size effect obtained by our calculations. We attempted to conventionally eliminate the size effect caused by the phonon mean free path, and as a result, the following linear correlation was successfully observed.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Generally, in soft matter, the phonon mean free path is usually lower than a few nanometers; this suggests that the phonon mean free path was not underestimated in our simulations. On the other hand, a recent experimental study of a liquid-crystalline molecule revealed low-frequency phonons to have a long mean free path: in the micrometer range, which may be correlated with the finite size effect obtained by our calculations. We attempted to conventionally eliminate the size effect caused by the phonon mean free path, and as a result, the following linear correlation was successfully observed.…”
Section: Resultssupporting
confidence: 85%
“…The thermal diffusivity and TC in LC phases are known to be larger in the direction parallel to the nematic director than perpendicular thereto. Thermal anisotropy has been studied both experimentally and computationally by using the Gay–Berne model. In experimental studies, Urbach et al discussed the thermal diffusivity behavior by employing a kinetic model based on an extension of the Eyring theory to anisotropic fluids . On the other hand, Sarman Laaksonen calculated the TC of LC phases of the Gay–Berne fluid and suggested that the anisotropy is derived from molecular movement because the movement along the direction perpendicular to the director is impeded by side-by-side collisions .…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of the single crystal elastic constants either requires large single crystals or methods applied to polycrystals that can measure elastic properties on length scales below the crystallite diameter. It is well known that single crystal elastic constants can be obtained by frequency-domain Brillouin scattering measurement (see, for example, 27,28 and the references therein). The elastic constants of ceria used in this study were reported in previous work based on time domain Brillouin measurements made on several crystallites with known orientations 17 .…”
Section: Resultsmentioning
confidence: 99%
“…The sound velocity of the Q‐T mode, v Q‐T , first increases, achieves a maximum at around α = 40°–50°, and then decreases, which is a typical feature of v Q‐T in transversely isotropic materials. [ 13,16,24 ] Unlike v Q‐L and v Q‐T , the sound velocity of the P‐T mode ( v P‐T ) shows a weak angular dispersion as v P‐T assumes values almost equal to v P‐T (α = 90°). The robust nature of v P‐T could be a general feature for soft matter, consistent with previous reports on collagen, [ 12 ] liquid crystal, [ 16 ] and spider silk.…”
Section: Resultsmentioning
confidence: 99%
“…It is particularly suitable for determining the elastic properties of transparent samples because the wave vector q of the scattering phonon can be selectively oriented over a wide range of angles. BLS has been utilized to determine the elastic stiffness tensor of many materials, including biofibers, [ 12 ] hybrid stacks of organic and inorganic materials, [ 13 ] molecular liquid crystals, [ 16 ] and crystalline inorganic membranes. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%